Genetic defects in fungal recognition and susceptibility to invasive pulmonary aspergillosis - Cunha, Cristina Amorim (2019)
The interindividual variability in the onset and clinical course of invasive pulmonary aspergillosis (IPA) raises fundamental questions about its actual pathogenesis. Clinical and epidemiological studies have reported only a few examples of monogenic defects, however an expanding number of common polymorphisms associated with IPA has been identified. Understanding how genetic variation regulates the immune response to Aspergillus provides critical insights into the human immunobiology of IPA by pinpointing directly relevant immune molecules and interacting pathways. Most of the genetic defects reported to increase susceptibility to infection were described or suggested to impair fungal recognition by the innate immune system. In this review, we discuss the contribution of host genetic variation in pattern recognition receptors to the development of IPA. An improved understanding of the molecular and cellular processes that regulate human susceptibility to IPA is ultimately expected to pave the way toward personalized medical interventions based on host-directed risk stratification and individualized immunotherapy.